Virtual reality for the treatment of chronic pain - a systematic literature review (Research, Society and Development, 2022)
Objectives: To map and discuss the different apps/games and virtual reality devices used in the treatment of chronic pain. Materials and Methods: A systematic literature review was conducted in the ACM Digital Library (Association for Computing Machinery), IEEE (Institute of Electrical and Electronic Engineers), PubMed and Science Direct databases. The search interval considered studies published from 2016 to 2021, with no language restriction. A total of 258 studies were identified. After the stages of the selection process, 5 studies met the inclusion criteria for analysis. Results: All studies showed positive results from the use of virtual reality in chronic pain. The metrics used for pain assessment were DVPMS, VAS, SFMPQ and WBF. The virtual reality devices used in the surveys were Pico G2 K, HTC Vive, Oculuis Go and Oculus Rift DK2. Conclusion: Virtual reality brings benefits when applied to the treatment of chronic pain.